TNM atlas: illustrated guide to the TNM, pTNM-classification of malignant tumours - Spiessl, Bernd; Beahrs, O. H.; Hermanek, Peter; Hutter, R. V. P.; Scheibe, Otto; Sobin, L. H.; Wagner, Gustav (UICC International Union Against Cancer / Union Internationale Contre le Cancer, 1989)
The present third edition of the TNM Atlas takes into consideration all additions and changes made in the fourth edition of the TNM Classification of Malignant Tumours and, therefore, represents the current state of the TNM classification as accepted worldwide by all national committees, including the American Joint Committee on Cancer. Numerous illustrations facilitate the practical application of the TNM system for all doctors working in the field of oncology